Linguistic choices for the identity of “China” in the discourse of Czech Sinologists - Lin, Melissa Shih-hui (Mongolian Journal of International Affairs, 2015)
This paper utilizes critical discourse analysis (CDA) to disclose the relationship between the lexical or textual device choices of the term “China” in the discourse of Czech Sinologists and how they tried to construct the identity of “China” in interviews collected by Professor Olga Lomová and her student Anna Zádrapová from 2010 to 2011. The analysis will focus on how the Czech Sinologists talk about their “China” and evaluate the term “China” in the discourse, within their experiences, and in the context of the social and cultural situation of the time. On the one hand, this paper will discuss the textual devices which convey the term “China” in the interviews of the Czech Sinologists, in the form of linguistic units, such as nouns, adjectives, noun phrases, verbal phrases and so on, and on the other hand, investigate how their identities of “China” are reflected through their choices of lexical or textual devices. Mongolian Journal of International Affairs Vol.19 2014: 153-165